Predictors of boredom at lectures: Medical Students’ experience - Ubah, Josephine Nonye (Advances in Social Sciences Research Journal, 2018)
Boredom is a negative experience common among students. Their attention need to be captivated for a reasonable length of time during lectures to grasp information being transmitted. Causes of boredom are many. Many ideas and activities have been suggested to cope with it. These include among others; reduction in the number of power point slides, introducing funny and interesting activities or sections and interacting with students one on one. The aim of this study was to identify the causes of boredom during lectures in a group of students in a medical school. There were 54 students consisting of 22 females and 32 males, with mean age of 27.39 (SD 2.978) years. The strongest predictors of boredom were prolonged lectures, organising lectures towards the end of the day, series of lectures without break and unconducive class rooms. Short span of attention and consuming large meals before lectures were not considered significant causes. The responses were similar in both sexes. Different causes of boredom have been identified. Lecturers should be conversant with these causes and introduce means to eliminate or reduce them to the barest minimum.